Establishment of a duplex TaqMan-based real time RT-PCR assay for simultaneous detection of BRSV and BVDV - Hao, Fuxing; Fu, Jinping; Chen, Jun; Zhu, Daoxian; Cai, Bingyan; Li, Yuxin; Liu, Chuanmin (Frontiers in Veterinary Science, 2024)
Bovine respiratory disease complex (BRDC) represents a global acute respiratory condition that imposes substantial economic burdens on the cattle industry due to its high morbidity and mortality rates. Various factors contribute to the development of BRDC, including pathogen infections, environmental stresses, weaning of calves, and herd relocation. Viral pathogens, notably bovine respiratory syncytial virus (BRSV) and bovine viral diarrhea virus (BVDV), play a critical role in the etiology of BRDC, with single or combined viral infections being particularly clinically significant. In this study, we developed a duplex TaqMan-based real-time RT-PCR assay targeting the conserved regions of the F gene of BRSV and the 5′ UTR sequence of BVDV. The limits of detection for BRSV and BVDV were 6.83 copies/μL and 5.24 copies/μL, respectively. Our validation data suggest the assay has excellent sensitivity, specificity and reproducibility. Testing of clinical samples revealed prevalence of BRSV and BVDV in local farms in Jiangsu Province, China. This study provides an efficient diagnostic tool for the epidemiological investigation of BRDC.